Antioxidative and hepatoprotective effects of enzymatic and acidic-hydrolysis of Pleurotus geesteranus mycelium polysaccharides on alcoholic liver diseases. (1st December 2018) - Song, Xinling; Liu, Zhonghai; Zhang, Jianjun; Zhang, Chen; Dong, Yuhan; Ren, Zhenzhen; Gao, Zheng; Liu, Min; Zhao, Huajie; Jia, Le
Highlights: The AcMPS and EnMPS showed potential anti-oxidant effects. The polysaccharides have hepatoprotection by remitting hepatic enzymes activities. Findings indicate the bioactivities are related to physical-chemical characteristics. The polysaccharides could be functional foods and natural drugs for preventing ALD. Abstract: The present work investigated the antioxidant and hepatoprotective effects of acidic- and enzymatic-hydrolysis mycelium polysaccharide (AcMPS and EnMPS) from Pleurotus geesteranus on alcoholic liver disease (ALD) mice. The animal studies demonstrated that the polysaccharides had potential effects reflected by remitting alcoholic hepatitis, reducing lipid accumulation, preventing oxidative stress, improving inflammatory symptoms, and alleviating the liver functions by histopathologic observation. Results showed that AcMPS (yield of 84%) was composed of L-Rha, D-Rib, L-Ara, D-Glc, D-Man and D-Gal with the Mw of 3.49 × 10 4 Da, while EnMPS (yield of 90%) was contained L-Rha, L-Ara, D-Gal and D-Glc with the Mw of 3.67 × 10 4 Da. Furthermore, the GC–MS analysis indicated that both AcMPS and EnMPS were β-pyranoside polysaccharides with the (1→3)- and (1→6)-linkages. The conclusions indicated that AcMPS and EnMPS could be used as natural drugs for preventing the ALD, and providing underlying hepatoprotective mechanisms, pharmaceutically.